Kleene algebras with implication - Castiglioni, José Luis (2017)
Inspired by an old construction due to J. Kalman that relates distributive lattices and centered Kleene algebras, in this paper we study an equivalence for certain categories whose objects are algebras with implication (H,⋀,⋁,→,0,1) which satisfy the following property for every a,b,c∈H : if a≤b→c , then a⋀b≤c .